TRADISI KROMOJATI DALAM PERNIKAHAN PERSPEKTIF MASLAHAH MURSALAH - Mutammimah, Bidayatul; Saiban, Kasuwi (Al-Maslahah : Jurnal Ilmu Syariah, 2024)
The Kromojati tradition in Gunung Kidul contains elements of benefit, both for husband and wife, for the community, and environmental preservation. The purpose of writing this article is to explain the Kromojati tradition in marriage in terms of the maslahah mursalah method. So that it can be analyzed the benefits that exist in this tradition. This research method uses a qualitative descriptive approach to explore the Kromojati tradition in marriage by analyzing the maslahah mursalah method. There are three research results in this article: [1] the Kromojati tradition is a requirement for the bride and groom who will enter into a marriage contract to bring ten teak seedlings, five of the seedlings are used as a means for conservation, and the other five seeds are intended for investment. [2] maslahah mursalah is maslahah that is not legal and is not opposed by the Shari'a but is supported by several arguments that show its benefit and do not cause real damage. [3] the form of benefit contained in the Kromojati tradition can be analyzed from the objectives and impacts that occur. From the objective aspect, the benefit that is born is environmental conservation and investment for the newlyweds. Meanwhile, from the aspect of impact, the benefit lies in increasing public awareness to preserve the environment, there is a balance between preserving the environment and saving for the bride and groom and the community so that it can be used as buildings that can develop advanced villages.